ANALISIS KEMAMPUAN LITERASI MEMBACA MELALUI TEKS DESKRIPSI BERDASARKAN PROSES KOGNITIF SISWA DI KELAS V SD NEGERI 060886 KOTA MEDAN - Raisyah Aulia Nabila Lubis; Dian Armanto; Anita Yus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading literacy is an essential competency that must be mastered by elementary school students, especially in facing the demands of 21st-century learning. However, students’ reading literacy skills in Indonesia are still relatively low, particularly at higher-order cognitive levels. This study aims to analyze the reading literacy skills of fifth-grade students based on cognitive process levels, namely finding information (L1), interpretation and integration (L2), and evaluation and reflection (L3) in descriptive texts. This study employed a descriptive qualitative approach. The subjects were 19 fifth-grade students of SD Negeri 060886 Kota Medan. Data were collected through a written test consisting of reading literacy questions developed based on learning objectives and cognitive processes. The results showed that students achieved high performance at the level of finding information (L1), with percentages reaching up to 100%. However, their performance tended to decrease at higher cognitive levels, particularly in interpretation and integration (L2) and evaluation and reflection (L3). Some students still experienced difficulties in connecting information, understanding implicit meanings, and providing critical responses to the text. These findings indicate that students’ higher-order thinking skills in reading literacy have not yet developed optimally. Therefore, it is necessary to design more systematic learning and assessment strategies to improve students’ critical reading skills.